The Market Value of Value Added Services on Digital Television Platforms: Hype versus Experience - Gálik, Mihály (Javnost-The Public, 2002)
This paper examines the acceptance and use of value added or interactive services by viewers on digital television (DTV) platforms. These services like the electronic program guide, enhanced background information on programs, internet access, video-ondemand, near video-on-demand, walled garden services have certain business value. The hype formulated in the mid-1990s gave them a priority over the good old television broadcasting service as main value drivers but due to viewersí unfavorable reaction to iTV the hype had not met expectations and incomes generated by value added services on different DTV platforms remained rather modest up till now. Nevertheless, the huge popularity and the high penetration of mobile phone use in Europe combined with special television show formats led to fast-growing uses of text messaging recently as a new way of interacting with television. The success of SMS demonstrates that viewers will change their coach potato habit if there is some real trade-off, some consumer surplus to get, and if the way of interacting is really user friendly. Itís worth mentioning yet that text message revenues do already represent an important element of proceeds generated by many shows on the screen.